Xueqin and Xakespeare - Forsyth, Judith (Taylor & Francis, 2024)
This monograph offers a detailed consideration of the five-volume novel written by Cao Xueqin and translated into English as The Story of the Stone, when read through William Shakespeare’s drama Hamlet, Prince of Denmark, A Tragedy in Five Acts. The book builds on the superlative David Hawkes/John Minford English language translation, which is inspired by resonances between the English Shakespearean literary heritage and the dynasties-old Chinese literary tradition inherited by Cao Xueqin. The Introduction sets out the potential for the significant cultural exchange between these two great literary works, each an inexhaustible inspiration of artistic and scholarly re-interpretation. Two chapters bring into consideration two universal literary themes: patriarchy – filial obedience and family honour, and tragic romantic love. These chapters are structured so that a key episode in Hamlet provides the initial perspective, which is then carried through to an episode in The Story of the Stone which offers points of complementarity: in-depth interpretation draws on inter-textual, historical and contemporary contexts referenced from the immense body of scholarly research which has accumulated around these iconic works. The third chapter proposes a new reading of the problematic ‘shrew’ character in the novel, Wang Xi-feng, through tracing the similarities of the structure of the narration of her life and death with a Shakespearean five-act tragedy.